VD_FINDINFO Jug / 2013 / 211 vom 9. April 2013 - VD Tribunal cantonal (2013)
PRÉSOMPTION D'INNOCENCE, CONSTATATION DES FAITS, FIXATION DE LA PEINE, SURSIS À L'EXÉCUTION DE LA PEINE | 42 CP, 43 CP, 47 CP, 10 CPP (CH), 398 al. 3 let. b CPP (CH)